(untitled) (Itinera, 2020)
Here we publish the libretto of Azio Corghi’s Opera Tra la Carne e il Cielo, written by Maddalena Mazzocut-Mis. The libretto assembles and transforms different passages from Pier Paolo Pasolini’s texts in order to investigate the relationship within poetry between word and music.